An Examination of Nurses' Knowledge and Attitude toward Pain Management at Hai Duong Provincial General Hospital in Vietnam Using a Cross-Sectional Approach - Nga Thi Nguyen; Huyen Thi Hoa Nguyen; Nhu Thi Thuy Pham; Anh Tuan Truong; Quang Duc Tran; Tran Ngoc Tran; Hoang Huy Duong (Kurdish Studies, 2024)
Nurses are essential in ensuring patients to receive proper pain management. There are, however, few studies assessing Vietnamese nurses' attitudes and knowledge on pain treatment, particularly among those employed in provincial hospitals. This cross-sectional descriptive study was conducted to determine the factors influencing the attitudes and knowledge of 200 nurses at Hai Duong Provincial General Hospital on pain treatment. Participants were randomly selected, and the structured Knowledge and Attitude Survey Regarding Pain (KASRP) was used to assess their attitudes and knowledge. The factors correlated with nurses' knowledge and attitudes on pain treatment were examined using logistic regression. The results showed that 78% of nurses had KASRP scores below 70%, indicating low degrees of knowledge and attitudes toward pain management. Higher levels of KASRP were positively correlated with higher educational attainment (OR=3.55, 95%CI=1.35-9.32, p=0.01) and attendance at previous pain management courses (OR=3.65, 95%CI=1.57-8.47, p = 0.03). These results imply that in order to give nurses the information and practical skills they need to enhance the standard of pain treatment for patients, pain management education programs are required.